2020
DOI: 10.1038/s41598-019-55601-0
|View full text |Cite
|
Sign up to set email alerts
|

Lavender essential oil induces oxidative stress which modifies the bacterial membrane permeability of carbapenemase producing Klebsiella pneumoniae

Abstract: Misuse of antibiotics in the clinical and agricultural sectors has caused the emergence of multidrugresistant (MDR) Klebsiella pneumoniae which contributes a threat to human health. in this study, we assessed the feasibility of lavender essential oil (LVo) as an antimicrobial agent in combinatory therapy with meropenem in suppressing the growth of carbapenemase-producing K. pneumoniae (Kpc-Kp). Synergistic interactions between LVO and meropenem were detected, which significantly reduce the inhibitory concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 57 publications
4
55
0
Order By: Relevance
“…Evolved strains with increased resistance and tolerance to carvacrol also showed mutations in transcriptional regulators induced by oxidative stress, such as soxR and yfhP , in E. coli [ 30 ] and S. enterica [ 10 ]. Oxidative stress was also induced by treatment with complex EO in Klebsiella pneumoniae [ 47 ]. These results highlight the relevance of oxidative stress in the cell response to natural antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolved strains with increased resistance and tolerance to carvacrol also showed mutations in transcriptional regulators induced by oxidative stress, such as soxR and yfhP , in E. coli [ 30 ] and S. enterica [ 10 ]. Oxidative stress was also induced by treatment with complex EO in Klebsiella pneumoniae [ 47 ]. These results highlight the relevance of oxidative stress in the cell response to natural antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…According to Meades, et al [ 52 ], cinnamon EO inhibits the carboxyltransferase subunit of E. coli , which partially explains that EO’s antibacterial activity. Moreover, as is well known, cell membranes are the first barrier and one of the main structures affected by natural antimicrobials, which alter their permeability and disrupt their integrity [ 35 , 47 ]. It is likely that the mutation of accA could result in improved cell membrane formation and/or repair in presence of OEO.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins that were lost play a role in energy generation; losing these proteins may disrupt the bacterial cell membrane and subsequent killing of the bacteria [ 75 ]. Moreover, the lavender EO (LVO) has been shown to cause oxidative stress to bacteria by oxidizing the outer membrane of the bacteria [ 120 , 121 , 122 ]. In fact, LVO and meropenem, in addition with reactive oxygen species (ROS), have resulted in bacterial membrane disruption.…”
Section: Essential Oil Researchmentioning
confidence: 99%
“…Hence, it is necessary to look into alternative solutions, such as natural products, for example, plant extracts, to overcome impending threats in the medical field [11,12]. It has been widely reported that plant extracts such as essential oils contain various bioactive compounds which are responsible for bioactivities, such as antimicrobial, anticancer, and anti-inflammatory agents [6,[12][13][14][15]. As nature is rich with different plants, researchers have focused their attention towards plant extracts as an alternative to synthetic drugs to be applied in the clinical setting [16].…”
Section: Introductionmentioning
confidence: 99%